Hi as you will see my maths is rubbish but I am trying to learn and would be most grateful for some help.
This is a basic algebra problem that I am trying to solve
x+3-k=6-3k
X=3-2k

I got as far as
X-k=3-3k
so
X-k+k=3-3k+k
so to get X=3-2k
3-3 must equal 3, this I don't understand, I would have thought 3-3=0?

Originally Posted by KDJA
Hi as you will see my maths is rubbish but I am trying to learn and would be most grateful for some help.
This is a basic algebra problem that I am trying to solve
x+3-k=6-3k
X=3-2k

I got as far as
X-k=3-3k
so
X-k+k=3-3k+k
so to get X=3-2k
3-3 must equal 3, this I don't understand, I would have thought 3-3=0?
On the left hand side you have 3 - 3 = 0, on the right hand side you have 6 - 3 = 3.

Originally Posted by KDJA
Hi as you will see my maths is rubbish but I am trying to learn and would be most grateful for some help.
This is a basic algebra problem that I am trying to solve
x+3-k=6-3k
X=3-2k

I got as far as
X-k=3-3k
so
X-k+k=3-3k+k
so to get X=3-2k
3-3 must equal 3, this I don't understand, I would have thought 3-3=0?
You seem to thinking of 3- 3k+ k as (3- 3)- (k+k) but that is not what is meant at all. "3k" means "3 times k" so you cannot combine that 3 with the other. Instead it is 3+(-3k+ k)= 3+ (-2k).